Crystal structure of [1,3-bis(2,4,6-trimethylphenyl)imidazolidin-2-ylidene]dichlorido{2-[1-(dimethylamino)ethyl]benzylidene}ruthenium including an unknown solvate - Kirill B. Polyanskii; Kseniia A. Alekseeva; Pavel A. Kumandin; Zeliha Atioğlu; Mehmet Akkurt; Flavien A. A. Toze (Acta Crystallographica Section E: Crystallographic Communications, 2019)
The title compound, [RuCl2(C21H26N2)(C11H15N)], is an example of a new generation of N,N-dialkyl metallocomplex ruthenium catalysts with an N→Ru coordination bond as part of a six-membered chelate ring. The Ru atom has an Addison τ parameter of 0.234, which indicates a geometry intermediate between square-based pyramidal and trigonal–bipyramidal. The complex shows the usual trans arrangement of the two chloride ligands, with Ru—Cl bond lengths of 2.3397 (8) and 2.3476 (8) Å, and a Cl—Ru— Cl angle of 157.47 (3)°. The crystal structure features C—H...Cl, C—H...π and π–π stacking interactions. The solvent molecules were found to be highly disordered and their contribution to the scattering was removed with the SQUEEZE procedure in PLATON [Spek (2015). Acta Cryst. C71, 9–18], which indicated a solvent cavity of volume 1096 Å3 containing approximately 419 electrons. These solvent molecules are not considered in the given chemical formula and other crystal data.